2016
DOI: 10.1097/md.0000000000004304
|View full text |Cite|
|
Sign up to set email alerts
|

Inversion of the Vδ1 to Vδ2 γδ T cell ratio in CVID is not restored by IVIg and is associated with immune activation and exhaustion

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Microbial translocation is now recognized as a driver of immune activation in HIV infection (49) and is associated with an abnormal distribution of d1 and d2 gd T cells in SIV infection (50). We have recently reported that similar perturbations in gd T cells also occur in CVID (32), and in the current study we observed a trend toward an association between the levels of sCD14, an indirect marker of microbial translocation, and MAIT cell loss in CVID. Two studies have reported elevated levels of LPS in CVID (30,31) and elevated LPS levels were associated with CD4 + T cell exhaustion.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Microbial translocation is now recognized as a driver of immune activation in HIV infection (49) and is associated with an abnormal distribution of d1 and d2 gd T cells in SIV infection (50). We have recently reported that similar perturbations in gd T cells also occur in CVID (32), and in the current study we observed a trend toward an association between the levels of sCD14, an indirect marker of microbial translocation, and MAIT cell loss in CVID. Two studies have reported elevated levels of LPS in CVID (30,31) and elevated LPS levels were associated with CD4 + T cell exhaustion.…”
Section: Discussionsupporting
confidence: 68%
“…Study cohort and samples CVID patients and healthy controls were enrolled at the Hospital das Clínicas, Medical School, University of São Paulo, and their demographics have been previously described (32), or at the Children's National Medical Center (Washington, DC) ( Table I). The study was approved by the Hospital das Clínicas, University of São Paulo Medical School Ethics Committee, and written informed consent was provided by all participants or their legal guardians in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Viallard et al [68] showed that patients with low CD27 + B-cell counts had higher percentages of HLA-DR CD8 T + cells with a differentiated effector phenotype, thus further confirming a higher activation status of CD8 + cells in CVID patients [69]. Finally, Paquin-Proulx et al [70] found a specific subset of γδ T cells expanded in CVID patients. Although they suggested that this deviation in γδ T-cell subsets is a general feature of CVID patients, further studies are needed to confirm this observation.…”
Section: T-cell Subsetsmentioning
confidence: 91%
“…An early in vitro study addressed the expression profile and functionality of PD-1/PD-L1 in γδ T-cells following stimulation with HMBPP and suggested that the PD-1/PD-L1 axis is important for regulation of anti-tumor mechanisms of γδ T-cells ( 196 ). Later it was found that PD-1 expression is more frequent on Vδ1, compared with Vδ2 T-cells ( 197 ) and equably distributed over several functionally distinctive subsets of Vγ9Vδ2 T-cells ( 44 ). A report that ex vivo cultivated Vδ2 T-cells depict stable, low cell surface expression of PD-1 following adoptive transfer ( 198 ) might fit the observations that PD-1 is only temporarily upregulated following in vitro stimulation as it has been reported both for HMBPP and ZOL ( 196 , 198 ).…”
Section: Targeting Activating and Inhibitory Receptorsmentioning
confidence: 99%